Renal cell carcinoma: Are we attacking a different tumor over the past 10 years? - Kotb, Ahmed Fouad (Int J Health Sci (Qassim), 2016)
OBJECTIVE: There is a noticeable increase in the presentation of different types of urological malignancies at a younger age of presentation, in our institution. The objective of our study was to investigate cases presented with renal cell carcinoma, managed in the past 10 years for any possible epidemiological and cancer characteristics changes. METHODOLOGY: Retrospective data collection for cases managed by our institution in the time period (2002–2012) was done. We included patients with complete data and pathologically proven renal cell carcinoma at final diagnosis. RESULTS: Complete data could be retrieved for 334 patients. The mean age of cases was 43.5 years, with 279 (83%), 200 (60%) and 128 (38%) of patients younger than 60, 50 and 40 years respectively. Males and females involvement were 191 (57%) and 143 (43%) respectively. By histopathology, 200 (60%) of patients had clear cell (CC) RCC and 134 (40%) patients had non-clear cell type (papillary or chromophobe). The mean tumor size was 10.9 cm and partial nephrectomy was applied for 16% of all the cases, including 65% for cases with tumor size less than 4 cm. CONCLUSION: There is a marked increase in the prevalence of renal cell carcinoma in the past 10 years, among younger age group, with higher rate for involvement of female gender. RCC is tending to present with large tumor size and more prevalence of non-clear cell histopathology. The use of partial nephrectomy is accepted for patients presented with renal mass and can safely challenge larger sized tumors.